Pemanfaatan Teknologi Informasi Dalam Perkembangan Bisnis Di Era Globalisasi - Amanda Adelia; Dina Aulia; Radiansyah; Nurbaiti (CV. ITTC INDONESIA, 2025)
One of the main factors contributing to this change is the advancement of information technology (IT). In the business context, IT not only serves as a tool to improve operational efficiency, but also as an enabler for innovation and the development of more effective marketing strategies. The purpose of this study is to how the use of information technology has a positive impact on business in the era of globalization. This study uses a descriptive qualitative method, which focuses on collecting and analyzing data from written sources, such as books, journal articles, research reports, and other relevant documents. By utilizing e-commerce platforms and digital marketing, UMKM can reach customers globally and increase their brand visibility and efficient logistics support is essential for e-commerce success. Further literature review is needed to find out what are the uses of information technology that can be used in business development in the era of globalization